Instructor Leadership and the Community of Inquiry Framework: Applying Leadership Theory to Higher Education Online Learning - Meech, Sally; Koehler, Adrie A. (International Review of Research in Open and Distributed Learning, 2023)
Higher education institutions continue to invest in online learning, yet research indicates instructors often lack experience, preparation, and guidance for teaching online. While instructor leadership is essential for meaningful online learning, few studies have investigated online instructors’ leadership behaviors. This study offers new insights into the conceptual and empirical alignment between instructor leadership, as interpreted through the dual lenses of organizational leadership theory and the Community of Inquiry (CoI) framework, proposing instructor leadership as foundational to the teaching and learning experience in a CoI. Specifically, the convergent mixed methods study investigated students’ (N = 87) and instructors’ (N = 7) perceptions of instructor servant leadership (SL) behaviors in an online graduate-level course designed to facilitate a CoI. Results demonstrate instructor SL behaviors were perceived differently by students and instructors, instructors’ self-perceptions were generally higher than students’ perceptions, and students’ perceptions of instructor SL were positively correlated with their satisfaction with the course and instructor. Implications offer insights into instructor leadership behaviors important for developing instructor leadership presence to facilitate meaningful learning and student satisfaction in higher education online learning.